In Vitro Regeneration of Korarima (Aframomum corrorima (Braun) P. C. M. Jansen): A Threatened Spice and Medicinal Herb from Ethiopia - Tilahun Hailu; Teklehaimanot Haileselassie; Tileye Feyissa (Scientifica)
Developing an in vitro regeneration system is very important to increase production and productivity of plants as well as for the conservation of rare and threatened medicinal plants like korarima (Aframomum corrorima (Braun) P. C. M. Jansen). To date, no study dealing with in vitro indirect regeneration system of korarima has been reported. Thus, in this study, we developed an efficient and reproducible protocol for in vitro regeneration of korarima via callus. The procedure involved soaking seeds in 50% H2SO4 for 16 h that resulted in 92.5% germination on plant growth regulators (PGRs)-free half-strength Murashige and Skoog (MS) basal medium after a month. Shoot and rhizome induction rate of 93.75% was obtained on the MS medium containing 1.5 mg/l BAP in combination with 0.1 mg/l IBA after five weeks. Whitish yellow friable callus was obtained from rhizome culture taken from in vitro grown plantlets. The MS medium containing 2.0 mg/l 2, 4D in combination with 0.5 mg/l kinetin, resulted in 77.5% callus induction. The shoot regeneration rate of 45% was obtained from callus on the MS medium containing 2.0 mg/l TDZ in combination with 0.5 mg/l IBA. The mean shoot number of 10.83 per explant was obtained upon multiplication on the MS medium containing 1.5 mg/l BAP with a mean shoot height of 5.37 cm. The best rooting responses were obtained on half MS medium supplemented with 0.5 mg/l IAA resulting in a mean number of root of 18.59, mean root length of 9.71 cm, and mean shoot height of 7.32 cm. The plantlets showed 75% survival efficiency after acclimatization. The present regeneration protocol offers a conceivable system towards effective conservation and genetic improvement of the crop by increasing the efficiency of genetic transformation.